Inhibition of cancer-cell migration by tetraspanin CD9-binding peptide. Issue 40 (19th April 2021) - Suwatthanarak, Thanawat; Tanaka, Masayoshi; Miyamoto, Yoshitaka; Miyado, Kenji; Okochi, Mina
Abstract : A CD9-binding peptide (RSHRLRLH), screened from EWI-2, was characterized, and its inhibition effect on cancer-cell migration and invasion was demonstrated. Abstract : A CD9-binding peptide (RSHRLRLH), screened from EWI-2, was characterized, and its effect on cellular migration and invasion was evaluated. As CD9 protein is overexpressed in cancer cells and plays an important role in cellular migration, the CD9-binding peptide preferentially inhibited the migration of cancer cells. Unlike conventional antiproliferative drugs, this CD9-binding peptide is promising as a novel precision antimigratory agent for cancer therapeutics.